True Organizational Learning Culture as a key to Unlocking Operational Performance: A Critical Review - Mary VITEROULI; Dimitrios BELIAS (Communications of International Proceedings, 2021)
The purpose of this study is to critically review and intensely emphasize the role organizational learning culture plays in promoting overall performance.  Investing in human, structural and relational capital, and harvesting commitment at the same time can bring about performance improvement. Information acquisition, distribution, and interpretation to organizational memory comprise the essence of organizational learning, which can, accordingly, bring about cognitive and behavioural changes by transforming tacit into explicit knowledge; or even forming new one via experimentation and information-sharing systems related to learning processes.  An enduring, strong-cultured organization involves the exchange of knowledge among organizations, teams, individuals and the environment.  Organizational performance is measured both in terms of quantitative and qualitative data, is influenced by a variety of factors either implicitly or explicitly and can be approached by subjective and objective ways.  To this end, organizations, whether private or public, by acknowledging that learning culture is critical for their success, can grow and thrive in an ever-changing environmental loop, and achieve overall (operational and financial) performance.
Keywords: Organizational performance; organizational learning culture.